Determination of the Aflatoxin B1 Level in Imported Milled Rice by ELISA in Duhok Province - Jaafar A. Ali; Nadhim Sulaiman A. Jakhsi (Zanco Journal of Pure and Applied Sciences, 2020)
Aﬂatoxins are fungal metabolites, toxic and carcinogenic. Aﬂatoxin B1 is the most common toxic mycotoxin classified as Group I carcinogen by the International Agency for Cancer Research. The purpose of this study is to determine the level of Aflatoxin B1 in different varieties of milled rice imported from different origins to Kurdistan region of Iraq between October and December 2018 by using indirect competitive enzyme-linked Immunosorbent Assay (ELISA). A total of 150 rice samples (30 each group) were collected from different sources (Thailand, Russia, India, Kurdistan and different sources from Iraqi public food distribution system), to evaluate their Aflatoxin B1. Out of 150 samples 90 (60%) have been detected with Aflatoxin B1, while the others 60 (40%) samples were not detected (under the detection limit of 0.02µg/kg). The concentrations were ranged from (0.03 to 3.12) µg/kg with an average range 0.94 µg/kg. The highest percentage of detected samples were from Russia 25 (28%) followed by a group of origins distributed through national distribution system 22 (24%), Thailand 21 (23%), Kurdish 12 (13%) and the lowest percentage was from India 10 (11%). However, out of 90 positive samples, only 4 (4%) samples from Russia were exceeded the European Union regulations limit of 2µg/kg of Aflatoxin B1 and other 86 (96%) were within the permissible levels of international legislations, these concentrations can cause a serious health issues to human because of the large amount of rice consumption per capita per year in Kurdistan region where rice is included in the daily diet, as a result, accumulation of Aflatoxin B1 in a human body will raise.